2000
DOI: 10.1074/jbc.m909613199
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acids in the Second and Third Intracellular Loops of the Parathyroid Ca2+-sensing Receptor Mediate Efficient Coupling to Phospholipase C

Abstract: To determine the role of amino acids in the second and third intracellular (IC) loops of the Ca 2؉ -sensing receptor (CaR) in phospholipase C (PLC) activation, we mutated residues in these loops either singly or in tandem to Ala and assessed PLC activity by measuring high extracellular [ (7), and a large group of pheromone receptors (8, 9) and, thus, constitute the family 3 of GPCRs (10). Receptors in the CaR/mGluR subfamily share several structural features. These include a large extracellular amino-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(62 citation statements)
references
References 29 publications
4
56
0
1
Order By: Relevance
“…Mutational analysis confirmed the functional importance of conserved residues (K586, M587, and K590) in the i2 loop of GABA B (2) and indicates that the GABA B(1) i2 loop lacks the requirements for interaction with G proteins (97,280). Mutation of K686, a basic residue in the i3 loop of GABA B(2) that plays a critical role in G protein coupling of mGlu1 and CaS receptors (66,102), suppresses functional coupling to G proteins in HEK293 and cerebellar granule cells, corroborating a similar role for this residue (97).…”
Section: The Ca 2ϩ Binding Sitementioning
confidence: 85%
“…Mutational analysis confirmed the functional importance of conserved residues (K586, M587, and K590) in the i2 loop of GABA B (2) and indicates that the GABA B(1) i2 loop lacks the requirements for interaction with G proteins (97,280). Mutation of K686, a basic residue in the i3 loop of GABA B(2) that plays a critical role in G protein coupling of mGlu1 and CaS receptors (66,102), suppresses functional coupling to G proteins in HEK293 and cerebellar granule cells, corroborating a similar role for this residue (97).…”
Section: The Ca 2ϩ Binding Sitementioning
confidence: 85%
“…CaSR is also related with PLC. Chang and co-workers (Chang et al, 2000) have reported that second and third intracellular loops of the CaSR is coupled with PLC. CaSR belongs to the type III family of G-proteincoupled receptors, which comprises the metabotropic glutamate receptor and putative vomeronasal organ receptors (Brown et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…A mutation (R866X) that truncates the C-terminal region after S865 (red) was also generated. All four mutants have been reported previously to impair PI-PLC signalling [17,19]. (B) Effects of iL point mutations and a C-terminus truncation mutant on CaSR total and surface expression.…”
Section: The Impacts Of Il-2 Il-3 and C-terminus Truncation Mutants mentioning
confidence: 99%
“…In the present study, we set out to investigate whether it is possible to define distinct subsets of molecular requirements for the Ca 2+ o -stimulated activation of G q/11 , G i/o and ERK 1/2 phosphorylation, taking advantage of previous work on the molecular requirements of Ca 2+ o -stimulated PI-PLC activation by the bovine CaSR [17], which exhibits 93% amino acid identity with the human CaSR (hCaSR). This work identified the conserved residue F707 (hCaSR residue F706) in iL-2, and three mutants homologous to hCaSR L797A, F801A and E803A, all of which exhibited marked attenuations in their Ca 2+ ostimulated PI-PLC responses [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation